Gleditsia aquatica, Water Locust - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
Water locust’s wide, spreading root system and affinity for hydric conditions makes it a useful specimen for erosion control on wet banks of freshwater systems. While not widely available, planting this tree in residential yards or other public locations may be less than ideal, since the long and sharply pointed thorns on the main trunk and branches can be hazardous. This deciduous tree is native to Florida. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.